Determination of parameters of an autonomous source of a constant magnetic field for a portable electromagnetic-acoustic transducer - Bolyukh, V. F.; Suchkov, G. M.; Mygushchenko, R. P.; Kalnytskyi, M. E. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Determination of rational parameters of an autonomous source of constant magnetic field, ensuring the efficiency of using portable electromagnetic-acoustic transducers (EMAT) for diagnostics of remote ferromagnetic objects. Methodology. An analysis of the parameters of an autonomous magnetic field source consisting of a permanent magnet and a ferromagnetic screen magnetizing a ferromagnetic object with a flat surface, providing a central magnetic field along the magnet axis above 0.3 T, was carried out. Results. The results of experimental studies on a sample of an autonomous source, which contained 6 sections of a permanent magnet made of NeFeB ceramics with dimensions of 505010 mm3, correspond to the results of calculating the magnetic field on the surface of a ferromagnetic sample with an error of up to 9 %. Experimental studies were carried out for EMAT with two magnetic field sourcescontaining rectangular permanent magnets of the same height but different widths. Novelty. It has been established that in order to select rational parameters of an autonomous source of magnetic field, it is necessary to use an integral criterion that takes into account the magnetic field in the surface layer of a ferromagnetic object, the magnetic scattering field, the volume of a permanent magnet, which determines the mass and size indicators and cost of the source, and the force of attraction to the ferromagnetic object. Practical value. For portable EMAT, increasing the magnetic field in a remote ferromagnetic object either by increasing the volume of a permanent magnet or by decreasing the air gap between the magnetic field source and the ferromagnetic object provides increased EMAT efficiency by increasing the ratio of the amplitude of the received ultrasonic bottom pulses to the noise amplitude.

Визначення раціональних параметрів автономного джерела постійного магнітного поля, які забезпечують ефективність використання портативних електромагнітно-акустичних перетворювачів (ЕМАП) для діагностики віддалених феромагнітних об’єктів. Методологія. Проведено аналіз параметрів автономного джерела магнітного поля, що складається з постійного магніту та феромагнітного екрана, що намагнічує феромагнітний об’єкт з плоскою поверхнею, забезпечуючи центральне магнітне поле вздовж осі магніту понад 0,3 Тл. Результати експериментальних досліджень на зразку автономного джерела, який містив 6 секцій постійного магніту з кераміки NeFeB розмірами 50-50-10 мм3, відповідають результатам розрахунку магнітного поля на поверхні феромагнітного зразка з похибкою до 9 %. Експериментальні дослідження були проведені для EMAП з двома джерелами магнітного поля, що містять прямокутні постійні магніти однакової висоти, але різної ширини. Новизна. Встановлено, що для вибору раціональних параметрів автономного джерела магнітного поля необхідно використовувати інтегральний критерій, який враховує магнітне поле в поверхневому шарі феромагнітного об’єкта, магнітне поле розсіювання, об’єм постійного магніту, який визначає масогабаритні показники та вартість джерела, силу притягання до феромагнітного об’єкта. Практична значимість. Портативний ЕМАП забезпечує збільшення відношення амплітуд інформаційних донних імпульсів до шуму шляхом нарощування об’єму його постійного магніту та зменшення повітряного зазору між джерелом магнітного поля і феромагнітним об’єктом.
Keywords: autonomous magnetic field source; permanent magnet parameters; magnetic field; remote ferromagnetic object; integral criterion; electromagnetic-acoustic transducer; signal amplitude; noise; автономне джерело магнітного поля; параметри постійного магніту; магнітне поле; віддалений феромагнітний об'єкт; інтегральний критерій; електромагнітно-акустичний перетворювач; амплітуда сигналу; шум